Developing PowerPoint-Based Learning Media to Improve Student Learning Comprehension - Ziana Maulidiyah; Luluk Choirun Nisak; Iin Bariroh Ma'arif; Yuyun Bahtiar (SCHOOLAR: Social and Literature Study in Education, 2026)
Learning is a process in which students interact with educators and various learning resources in an environment that supports learning activities. This research is motivated by the challenges in learning Aqidah Akhlak at Islamic Junior High School Rahmat Said Bongkot Peterongan, where students often experience difficulties in understanding the material and low interest in learning due to the use of learning media that are less creative and monotonous. The main objective of this research is to develop an effective PowerPoint-based interactive learning media to improve student understanding. This research uses the Research and Development (R&D) method with the ADDIE model approach. The validation results show that the media is very valid with an average acceptance rate of Aqidah Akhlak teachers of 93.7% and ICT teachers of 81.8%. In addition to validation, this media was also tested for practicality and was declared practical with an assessment of 88.8% from Aqidah Akhlak teachers. The effectiveness test was conducted on 29 eighth-grade students, and the results showed that 26 students (89.6%) succeeded in achieving learning completion, which is included in the "very good" category. The student response questionnaire also showed a positive response to the use of this media. Thus, it can be concluded that this PowerPoint-based interactive learning media is highly effective and suitable for use in teaching aqidah and akhlak. This media has been proven to increase student understanding and interest in learning, thus providing an innovative solution to address existing learning challenges.